Total AV Block: A Case of Challenging Diagnosis and Management at Rural Hospital in East Kalimantan - Kartawan, Gabrielle Alexander (Universitas Aisyah Pringsewu (UAP) Lampung, 2021)
Total AV Block is a condition where there is a complete failure of conduction between atria and ventricle so there is no relationship between P waves and QRS complexes. In adults, the most common causes are degenerative and acute myocardial infarction (ischemic). We report a case of diagnosis and management of Total AV Block in a rural hospital in East Kalimantan, Indonesia with limited settings and facilitation. A 63-year-old female presented with chest discomfort and high BP with a history of uncontrolled hypertension. The ECG revealed a Total AV Block with 37 ventricular bpm and approximately 80 atrial bpm. Atropine and Epinephrine failed to resolve the rhythm and improve the rate. Further evaluation and pacing are indicated but the referral process and requirements were impossible to meet then. Supporting and symptomatic drugs based on possible causes such as anti-hypertension, anti-angina, anti-platelet and close observation in an intensive care unit (ICU) could help stabilize the hemodynamic and diminished the patient’s complaint throughout hospital stays until the conditions suitable for the referral process.